PENGARUH PENGGUNAAN MEDIA FUN THINKERS BOOK BERBASIS PLAY BASED LEARNING TERHADAP KEMAMPUAN BERCERITA SISWA KELAS III SD INPRES TETEBATU KABUPATEN GOWA - Nur Fijriani; Ummu Khaltsum; Nur Khadijah Razak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Fun Thinkers Book media based on Play-Based Learning on students’ storytelling skills using a quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design). The sample consisted of 44 students, including 24 in the experimental class and 20 in the control class, selected through purposive sampling. Data were collected through tests (pretest–posttest) and observation, and analyzed using descriptive and inferential statistics with SPSS. The results showed an improvement in storytelling skills in the experimental class from 64.00 to 89.00 (mastery from 42% to 100%), while the control class improved from 56.00 to 71.00 (mastery from 25% to 60%). The t-test indicated a significance value of 0.001 < 0.05 and t-count of 4.218 > t-table of 2.018, meaning that H0 was rejected and H1 was accepted. Based on these findings, it can be concluded that the Fun Thinkers Book media based on Play-Based Learning has a significant and positive effect on students’ storytelling skills, as well as increasing their activeness and engagement in learning